PENDEKATAN REKONSTRUKSI SOSIAL DALAM PENGEMBANAGAN KURIKULUM PENDIDIKAN AGAMA ISLAM - KHAIRUDDIN BANGUN; TASMAN HAMAMI (Raudhah - Proud To Be Professional, 2022)
The curriculum serves as both a tool for achieving educational objectives and a manual for implementing instruction at all levels and types of education. There are a number of approaches to curriculum development that are meant to follow these systematic development processes to get a better curriculum by approaching the proper tactics and methods. The social rebuilding technique is one of the strategies the creator came up with. This study intends to investigate how social reconstruction methodology was used to create an Islamic religious education curriculum. This study's foundation is a review of the literature that uses data from library sources, including books, research journals, and other documents pertinent to the study's topic. The findings of this study show that the Social Reconstruction Approach to developing a curriculum or skills education program begins with the societal issues that need to be solved before applying science and technology while collaborating to find those answers.